Thành phần hóa học dịch chiết etyl axetat cây bảy lá một (Paris polyphylla var. chinensis Franchet) trồng tại Việt Nam - Duyên, Nguyễn Thị; Hà, Đỗ Thị; Thắng, Trần Vũ; Chiến, Nguyễn Quyết; Long, Phạm Quốc (Vietnam Journal of Chemistry, 2017)
Phytochemical investigation of the ethyl acetate extract of Paris polyphylla var. chinensis Franchet led to the isolation of 6 compounds, including stigmasterol (1), pennogenin (2), quercetin (3), (+)-trans-ε-viniferin (4), diosgenin-3-O-α-L-rhamnopyranosyl-(1→2)-β-D-glucopyranoside (ophiopogonin C’, 5), and diosgenin-3-O-α-L-rhamnopyranosyl-(1→2)-[β-D-glucopyranosyl-(1→3)]-β-D-glucopyranoside (gracillin, 6). Their structures were elucidated by 1D, 2D-NMR spectra, HR-ESI-MS and APCI-MS, and in comparison with reported data. Keywords. Paris polyphylla var. chinensis, gracillin, pennogenin, ophiopogonin C’, spirostan steroid.